Vagus nerve stimulation exerts cardioprotection against myocardial ischemia/reperfusion injury predominantly through its efferent vagal fibers - Watthana Nuntaphum (2018)
© 2018, Springer-Verlag GmbH Germany, part of Springer Nature. Vagus nerve stimulation (VNS) has been shown to exert cardioprotection against myocardial ischemia/reperfusion (I/R) injury. However, whether the cardioprotection of VNS is mainly due to direct activation through its ipsilateral efferent fibers (motor) rather than indirect effects mediated by the afferent fibers (sensory) have not been clearly understood. We hypothesized that VNS exerts cardioprotection predominantly through its efferent vagal fibers. Thirty swine (30–35 kg) were randomized into five groups: I/R no VNS (I/R), and left mid-cervical VNS with both vagal trunks intact (LC-VNS), with left vagus nerve transection (LtVNX), with right vagus nerve transection (RtVNX) and with atropine pretreatment (Atropine), respectively. VNS was applied at the onset of ischemia (60 min) and continued until the end of reperfusion (120 min). Cardiac function, infarct size, arrhythmia score, myocardial connexin43 expression, apoptotic markers, oxidative stress markers, inflammatory markers (TNF-α and IL-10) and cardiac mitochondrial function, dynamics and fatty acid oxidation (MFN2, OPA1, DRP1, PGC1α and CPT1) were determined. LC-VNS exerted cardioprotection against myocardial I/R injury via improvement of mitochondrial function and dynamics and shifted cardiac fatty acid metabolism toward beta oxidation. However, LC-VNS and LtVNX, both efferent vagal fibers are intact, produced more profound cardioprotection, particularly infarct size reduction, decreased arrhythmia score, oxidative stress and apoptosis and attenuated mitochondrial dysfunction compared to RtVNX. These beneficial effects of VNS were abolished by atropine. Our findings suggest that selective efferent VNS may potentially be effective in attenuating myocardial I/R injury. Moreover, VNS required the contralateral efferent vagal activities to fully provide its cardioprotection.